Graduate employment rate of one state university of the Calabarzon region in Philippines: A retrospection - Adriel G. Roman; Rogacion U. Villanueva (International Journal of Evaluation and Research in Education (IJERE), 2023)
Every higher education institution (HEI) needs to monitor the employability status of its graduates as this reflects the quality education that HEIs provide to their students. In this study, a retrospective approach was used to analyze the employment status of graduates of a state university in the Philippines from 2015 to 2019. A data mining procedure was adopted to obtain necessary data and analysis. It was hypothesized in the study that the employment rates are the same across programs per year. Also, the employment rates from 2015 to 2019 are the same as the targeted employment rate in the strategic plan of the university. Statistical treatments such as mean, median, and standard deviation, Shapiro-Wilk test, and Analysis of Variance (ANOVA) were used to test the hypothesis. Results show that the employment rate of graduates of 2015-2019 is in the high-level category and significantly higher than the targeted employment rate in the university strategic plan. Similarly, findings show significant differences in the employability rates of graduates considering the programs they enrolled in. On the contrary, no significant difference in the employment rate of graduates per year graduated. The study concluded that the university is consistent in producing employable graduates.